The Last Days of Mankind / Ecological Survival of Extinction - Mines Samuel; Simon And Schuster (1971)
Ecology: An Introduction, The Waters and Wetlands, Rivers and Dams and Floods, Water Pollution and the Great Water Shortage, The Everglades, The Woodlands, The Forests, Drama in the Redwoods, The Wildlife, The Blight of Civilization, The Ecology of the City, The Road Builders, Man and Pesticides, In the Public Domain, Public Lands and Public Parks, Protection or Multiple Use?, Life in the Balance, Index.